Nicotinamide Phosphoribosyltransferase Attenuates Methotrexate Response in Juvenile Idiopathic Arthritis and In Vitro. Issue 3 (11th May 2016) - Funk, RS; Singh, R; Pramann, L; Gigliotti, N; Islam, S; Heruth, DP; Ye, SQ; Chan, MA; Leeder, JS; Becker, ML
Abstract : Variability in response to methotrexate (MTX) in the treatment of juvenile idiopathic arthritis (JIA) remains unpredictable and poorly understood. Based on previous studies implicating an interaction between nicotinamide phosphoribosyltransferase (NAMPT) expression and MTX therapy in inflammatory arthritis, we hypothesized that increased NAMPT expression would be associated with reduced therapeutic response to MTX in patients with JIA. A significant association was found between increased plasma concentrations of NAMPT and reduced therapeutic response in patients with JIA treated with MTX. Inhibition of NAMPT in cell culture by either siRNA‐based gene silencing or pharmacological inhibition with FK‐866 was found to result in a fourfold increase in the pharmacological activity of MTX. Collectively, these findings provide evidence that NAMPT inhibits the pharmacological activity of MTX and may represent a predictive biomarker of response, as well as a therapeutic target, in the treatment of JIA with MTX.